2011
DOI: 10.1007/s10578-011-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Internalizing and Externalizing Problems at Five Years by Child and Parental Factors in Infancy and Toddlerhood

Abstract: This study examined child and parental factors in infancy and toddlerhood predicting subclinical or clinical levels of internalizing and externalizing problems at 5 years of age. Ninety-six children and their families participated. They were assessed when the children were 4-10 weeks old (T1), 2 years (T2) and 5 years old (T3). Child risks (difficult temperament, health problems, early emotional and behavioral problems), parental risks (psychopathology, parenting stress and perception of the child) and family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 69 publications
5
49
1
2
Order By: Relevance
“…Contrary to prediction and prior research (Mantymaa et al, 2012; Shaw, Owens, Giovannellli, & Winslow, 2001), maternal depressive symptoms, maternal unresponsiveness, and overtly negative behavior were not significantly associated with child externalizing at 2 years in the path model. Consistent with the results for internalizing symptoms, infant negative emotionality did not exacerbate links between maternal depressive symptoms and child externalizing behaviors, or the links between both insensitive maternal behaviors and child externalizing behaviors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to prediction and prior research (Mantymaa et al, 2012; Shaw, Owens, Giovannellli, & Winslow, 2001), maternal depressive symptoms, maternal unresponsiveness, and overtly negative behavior were not significantly associated with child externalizing at 2 years in the path model. Consistent with the results for internalizing symptoms, infant negative emotionality did not exacerbate links between maternal depressive symptoms and child externalizing behaviors, or the links between both insensitive maternal behaviors and child externalizing behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the hypothesis, and prior research (Mantymaa et al, 2012), maternal depressive symptoms were linked with more unresponsive maternal behaviors. Unresponsive maternal behaviors, including limited reaction to infant cues and distracted actions, may stem from the tendency of mothers with elevated depressive symptoms to focus on their own needs more so than their infants’ (Dix, Moed, & Anderson, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PSI × time ¼ ns. Mäntymaa et al (2012) found that 24-month-old children's internalising problem behaviour were more highly related to parenting stress at an infants' age of 4-10 weeks than externalising problem behaviour. In our analyses controlling for the number of siblings, however, parent reported children's externalising problems decreased over time, regardless of maternal stress level, whereas parent report of internalising problems remained stable over time.…”
Section: Discussionmentioning
confidence: 87%
“…have an impact on this dyad (Abidin, 1999). Maternal stress and maternal psychiatric well-being is associated with young children's behavioural development, such as greater infant reactivity to novelty, externalising and internalising behavioural problems, and motivation and competence in social situations (Keim et al, 2011;Mäntymaa et al, 2012;Saisto, Salmela-Aro, Nurmi, & Halmesmäki, 2008;Sparks, Hunter, Backman, Morgan, & Ross, 2012;Yaman, Mesman, van Ijzendoorn, & Bakermans-Kranenburg, 2010;Werner et al, 2012). Maternal distress may increase negative judgments about infant behaviour, and mothers reporting high parenting stress may be less responsive ('sensitive') to their infants' needs/demands (Pereira et al, 2012;Werner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%